Social Transformation and Managerial Strategies in Fire Management: A Comparative Study in Disaster Prone Areas - Supriatna, Agus; Duwila, Iwan; Sianipar, Godlif; Hidayat, Muhamad (Socious Journal, 2025)
Fire risks in disaster-prone areas are increasing due to climate change and anthropogenic activities, such as illegal land clearing and weak law enforcement, especially in Indonesia, Brazil, and Australia. This study uses a qualitative approach with literature review methods and thematic content analysis to explore the dynamics of social transformation and managerial strategies in fire management through a comparative cross-case study. Social transformation is driven by citizen participation and local actors integrating local knowledge with modern technology, such as the Masyarakat Peduli Api program in Indonesia that reduced fires by 40% and "FireWise" in Australia that accelerated collective awareness. However, conflicting interests, such as plantation expansion, and weak institutional structures hinder effectiveness, especially in Indonesia and Brazil. Co-management and CBFiM strategies have proven to be more adaptive than centralized technocratic approaches, which often fail in Sub-Saharan Africa. Responsive managerial institutions, such as in Australia, support inclusive policies, while hierarchical systems in Latin America hinder adaptation. Community resilience depends on citizen empowerment, equitable resource distribution, and collaborative governance, making social transformation and community-based approaches key to sustainable fire management.